2014
DOI: 10.5761/atcs.oa.12.02219
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of FDG-PET in Surgically Treated Pathological Stage I Lung Adenocarcinoma

Abstract: Purpose: This retrospective study evaluated whether the maximum standardized uptake value (SUVmax) on 18F-deoxyglucose (FDG)-positron emission tomography (PET) could be used to predict the prognosis of patients with pathological stage I adenocarcinoma. Methods: We analyzed 138 consecutive patients with pathological stage IA or IB lung adenocarcinoma except pure bronchioloalveolar carcinoma (BAC) who underwent preoperative FDG-PET imaging and curative resection from January 2005 to October 2010. We analyzed ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…Recently, FDG-PET has become a valuable tool for evaluating patients with NSCLC, and many studies have indicated the utility of FDG-PET for evaluating the clinical stage (de Geus-Oei et al, 2007;Al-Jahdali et al, 2012), chemotherapy effect and recurrence (Hoekstra et al, 2005;Al-Jahdali et al, 2012), and also for predicting the prognosis in patients with resected NSCLC (AlSarraf et al, 2008;Higuchi et al, 2014). However, in this study, we demonstrated differences in the prognostic significance of the SUVmax according to the histologic type of NSCLC.…”
Section: Discussioncontrasting
confidence: 52%
“…Recently, FDG-PET has become a valuable tool for evaluating patients with NSCLC, and many studies have indicated the utility of FDG-PET for evaluating the clinical stage (de Geus-Oei et al, 2007;Al-Jahdali et al, 2012), chemotherapy effect and recurrence (Hoekstra et al, 2005;Al-Jahdali et al, 2012), and also for predicting the prognosis in patients with resected NSCLC (AlSarraf et al, 2008;Higuchi et al, 2014). However, in this study, we demonstrated differences in the prognostic significance of the SUVmax according to the histologic type of NSCLC.…”
Section: Discussioncontrasting
confidence: 52%
“…Our data suggested the SUVmax cutoff value of 2.32 appears to be a valuable index in the detection of tumors with lymphovascular invasion. This cutoff value was comparable with that published in a previous study: Higuchi et al [24] reported that the SUVmax cutoff value of 2.5 could be used to predict for 5-year disease-free survival. Our study had several limitations.…”
Section: Correlation Between Tumor Suvmax and Lymphatic Invasion In Ssupporting
confidence: 81%
“…However, in the literature, there is not much evidence on the role of pretreatment parameters in prediction of response, whereas more data exist regarding prechemotherapy parameters and prediction of prognosis. [29][30][31][32][33] Additionally, we also showed that lymph node uptakes in patients post-treatment, expressed both as absolute values and percentage changes, were significantly different between the 2 groups (responders vs. non-responders). Although most studies in the literature have evaluated the metabolic activity of regional lymph nodes as a prognostic index, Kamel et al 15 showed that less than Metabolic Response in NSCLC After Neoadjuvant Therapy 60% reduction in N2 SUVmax after induction therapy was an independent predictor of residual N2 disease, which is often associated with poor survival outcomes.…”
Section: Angelo Castello Et Almentioning
confidence: 54%